THE EFFECT OF NUMBERED HEAD TOGETHER TO INCREASE STUDENTS’ ABILITY IN READING NARRATIVE TEXT - Hafiza Hafiza; Fakhri Ras; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This pre-experimental research aimed to find out whether or not there is a significant effect of Numbered Head Together technique on the first year students’ ability in comprehending narrative texts at SMAN 2 Tambang. The research design was one group pre-test post-test design. The population was the first year students in academic year 2019/2020. The selected sample was X Bahasa students which consisted of 35 students. The instrument used to collect the data was a reading test. The tests consisted of 40 items. The obtained data was analyzed by using SPSS version 23.0. The finding of the research showed that the mean score of post-test was higher than pre-test (80.5>65.6). The value of t-test was higher than t-table (13.616>2.06) at 5% of significance level. Therefore, alternative hypothesis (Ha) was accepted. This means that Numbered Head Together Technique was effective for teaching reading comprehension concerning narrative text. There is a significant effect of Numbered Head Together technique on the first year students’ ability in comprehending narrative texts at SMAN 2 Tambang. There are some suggestions that can be given in relation to the writer’s conclusion. One of them is Number Head together can be alternative strategy in teaching English. It can be used in teaching reading narrative text, or it also can be used in teaching other language skills or other language components and other type of textsKey Words: Effect, Numbered Head Together Technique, Reading Narrative Texts